Analisis Etika Bisnis pada Harga Terhadap Keputusan Pembelian di Perusahaan Minyak Goreng - Fitri Nabila Khairunnisa; Halimah Zahrah; Kayla Rizqy Agustina; Nida Hulwa Luthfiyah (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study investigates the impact of business ethics and pricing on cunsomer purchasing decisions for cooking oil in Indonesia, focusing on the crisis of scarcity and price spikes during 2021-2022. As a staple commodity, cooking oil plays a vital role in the socio-economic landscape. Unethical practices such as hording and price manipulation by cartels have triggered public distrust and panic buying. Business ethics demand that companies act with fairness, social responsibility, and integrity, directly shaping cunsomer perceptions of fair and transparent pricing. Findings reveal that cunsomer consider ethical factors in their purchases, often preferring products from ethical companies even at higher prices. However, regulations like Indonesia’s Anti-Monopoly Law and Cunsomer Protection Law have not been fully effective in curbing these violations. The islamic economi perspective also highlight the importance of price justice and avoiding exploitation. This study uses a equalitative approach to analyze the interplay between business ethics, pricing, and purchasing decision, aiming to offer both theoretical insights and practical recommendations. The results suggest that businesses should prioritize ethucal considerations in pricing to build lasting cusomer trust. These findings are essential for echancing oversight and developing fair pricing polices in the cooking oil sector, contributing to more sustainable cunsomer confidence and market stability